2017
DOI: 10.1002/pbc.26634
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the psychosocial standards in pediatric cancer: Current staffing and services available

Abstract: Background Fifteen evidence-based Standards for Psychosocial Care for Children with Cancer and their Families were published in 20151. The Standards cover a broad range of topics and circumstances and require qualified multidisciplinary staff to be implemented. This paper presents data on the availability of psychosocial staff and existing practices at pediatric oncology programs in the United States, providing data that can be used to advocate for expanded services and prepare for implementation of the Standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 26 publications
6
89
0
Order By: Relevance
“…This is a single‐institution study from a large academic referral center that is well‐staffed with designated resource specialists and psychosocial clinicians, which may limit the generalizability of our findings. A recent survey of the availability of psychosocial staff at 144 pediatric oncology programs concluded that not having a comprehensive multidisciplinary team was a barrier to the full implementation of psychosocial standards of care despite most programs having basic staffing . With regard to the prevalence of poverty in our sample, our data are limited by the fact that the PAT was administered only in English and Spanish that likely resulted in an underrepresentation of racial and ethnic minorities in our sample.…”
Section: Discussionmentioning
confidence: 88%
“…This is a single‐institution study from a large academic referral center that is well‐staffed with designated resource specialists and psychosocial clinicians, which may limit the generalizability of our findings. A recent survey of the availability of psychosocial staff at 144 pediatric oncology programs concluded that not having a comprehensive multidisciplinary team was a barrier to the full implementation of psychosocial standards of care despite most programs having basic staffing . With regard to the prevalence of poverty in our sample, our data are limited by the fact that the PAT was administered only in English and Spanish that likely resulted in an underrepresentation of racial and ethnic minorities in our sample.…”
Section: Discussionmentioning
confidence: 88%
“…A national survey open to all pediatric oncology treatment programs in the United States (n = 200)— Preparing to Implement Psychosocial Standards: Current Services and Staffing (PIPS‐CSS) —was conducted from June to December 2016. Details of the study methodology are available in Scialla et al . Independent assessments from up to three specific oncology professionals (one per discipline) with leadership roles at each program—a pediatric oncologist (Medical Director/Clinical Director), a psychosocial leader (Director of Psychosocial Services/staff member with most seniority), and an administrator (Administrative Director/Business Administrator/Director of Operations)—were included.…”
Section: Methodsmentioning
confidence: 99%
“…Our results show that patients in the elementary age (4-7 years) group presented significantly higher distress levels than the other groups ( Table 2). One possible explanation is that younger children (0-3 years) may be reassured by simpler measures such as physical contact by the caregiver, while older children (8)(9)(10)(11) and ≥12) may find verbal explanation a helpful coping strategy. [73][74][75][76][77] Children aged 4 to 7 may be vulnerable in that they are not fully dependent on caregivers yet also not fully autonomous.…”
Section: Discussionmentioning
confidence: 99%
“…Children with cancer suddenly find themselves in a novel rigorous environment, in which unfamiliar adults make all the decisions, even the most negligible ones. Uncertainty becomes a rule for these patients, the need for a safe space becomes predominant, and psychological assistance aims to create a holding environment containing doubts, anguish, and fears . Managing these disturbing emotions is particularly important during the invasive procedures associated with diagnosis and treatment …”
Section: Introductionmentioning
confidence: 99%